Stress management of client with mental disorder after Hospitalization - Widyo Subagyo; Dyah Wahyuningsih; Mukhadiono Mukhadiono (Jurnal Riset Kesehatan, 2013)
Research aimed to describe stress management of client with mental disorder after hospitalization. This study used the collecting data with in depth  interview to 10 participants and families . This research showed that stressor of client with mental disorder were undisciplined taking, medicine, unacceptable of environment, shy and  being excluded. Appraissal of stressor were shy, angry and feeling of unbelieve by other. Coping resources were family, society evironment and positive believe. Coping mechanism that used were sharing with others, do activity and blame others. Patient with mental disorder relap because of lack of self management, family support, and in conductive environment.